Kristus ukřižovaný na palmě, „locus tristis“ a emblematika 17. století - Pavel Panoch (Theatrum Historiae)
The paper deals with a curious iconography of a stone relief decorating the statue of St. John of Nepomuk in Pecka town in the Eastern Bohemia. The unusual sculptural motif of Christ crucified on a palm leaf, which is held in the St. John’s hand by his side, was a traditional sign of Christian Martyrs and its origin is rising from the mystical tradition of a Cartusian order. A founder of the Cartusian order, St. Bruno, was presented with this unusual type of the Cross in visual culture since the Medieval times. The motif was transformed during the Early Baroque Era to a poetical picture and during the first half of the 17th Century it has been applied in several Emblem books encluding enormously favourite and influential treatise Pia desideria written by Jesuit Herman Hugo and edited in Antwerp in 1624.